A new efficient asymmetric cryptosystem based on the integer factorization problem of N=p2q - Kamel Ariffin, Muhammad Rezal; Asbullah, Muhammad Asyraf; Abu, Nur Azman; Mahad, Zahari (Institute for Mathematical Research, Universiti Putra Malaysia, 2013)
In this paper, we introduce a new scheme based on the hardness of factoring integers of the shape N = p2q. Our scheme uses a combination of modular linear and modular squaring. We show that the decryption is 1-to-1 which is a great advantage over Rabin's cryptosystem. Its encryption speed has a complexity order faster than RSA and ECC. For decryption its speed is better than RSA and is marginally behind ECC. Constructed using a simple mathematical structure, it has low computational requirements and would enable communication devices with low computing power to deploy secure communication procedures efficiently.